2011
DOI: 10.1128/aac.01589-10
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thymidylate Synthase Gene Polymorphisms with Stavudine Triphosphate Intracellular Levels and Lipodystrophy

Abstract: The antiviral activity and toxicity of stavudine (d4T) depend on its triphosphate metabolite, stavudine triphosphate (d4T-TP). Therefore, modifications in intracellular levels of d4T-TP may change the toxicity profile of stavudine. d4T-TP intracellular levels in peripheral blood mononuclear cells were determined with a prominence liquid chromatograph connected to a triple-quadruple mass spectrometer. Polymorphisms in the thymidylate synthase (TS), methylenetetrahydrofolate reductase (MTHFR), dihydrofolate redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
2
13
1
Order By: Relevance
“…In a later study, Domingo et al showed that a thymidylate synthetase genetic polymorphism was associated with d4T-TP intracellular levels [32]. Among the low-expressing thymidylate synthetase genotypes, those that were associated with higher propensity for toxicity had higher intracellular d4T-TP levels, similar to those found in adults taking 40 mg b.i.d.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a later study, Domingo et al showed that a thymidylate synthetase genetic polymorphism was associated with d4T-TP intracellular levels [32]. Among the low-expressing thymidylate synthetase genotypes, those that were associated with higher propensity for toxicity had higher intracellular d4T-TP levels, similar to those found in adults taking 40 mg b.i.d.…”
Section: Discussionmentioning
confidence: 82%
“…Among the low-expressing thymidylate synthetase genotypes, those that were associated with higher propensity for toxicity had higher intracellular d4T-TP levels, similar to those found in adults taking 40 mg b.i.d. [32]. The same polymorphism has also been associated with peripheral neuropathy in patients on stavudine-based therapy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the association of HLA-B*40∶01 with HALS has been reported in a South East Asian population treated with d4T [6]. We have showed the association of thymidylate synthase (TS) polymorphisms with HALS in a limited sample of patients [7], [8].…”
Section: Introductionmentioning
confidence: 82%
“…Low expression TS genotype was associated with the development of HIV-1/cART-associated lipodystrophy syndrome (OR = 14.0; 95%CI: 2.09 --108, p = 0.0032). Our preliminary data show that polymorphisms in the thymidylate synthase gene are strongly associated with d4T-TP intracellular levels and with the development of lipodystrophy [95].…”
Section: Polymorphism In Other Genesmentioning
confidence: 98%
“…Therefore, modifications at intracellular levels of d4T-TP may change the toxicity profile of d4T. We determined d4T-TP intracellular levels in peripheral blood mononuclear cells using a prominence liquid chromatograph connected to a triple-quadruple mass spectrometer [95]. Also, polymorphisms in the thymidylate synthase (TS), methylenetetrahydrofolate reductase (MTHFR), dihydrofolate reductase (DHFR), reduced folate carrier 1 (RFC1, SLC19A1) and Cyclin D1 (CCND1) genes were determined by direct sequence analysis.…”
Section: Polymorphism In Other Genesmentioning
confidence: 99%